2011
DOI: 10.1071/wf09125
|View full text |Cite
|
Sign up to set email alerts
|

Simulating landscape-scale effects of fuels treatments in the Sierra Nevada, California, USA

Abstract: In many coniferous forests of the western United States, wildland fuel accumulation and projected climate conditions increase the likelihood that fires will become larger and more intense. Fuels treatments and prescribed fire are widely recommended, but there is uncertainty regarding their ability to reduce the severity of subsequent fires at a landscape scale. Our objective was to investigate the interactions among landscape-scale fire regimes, fuels treatments and fire weather in the southern Sierra Nevada, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 61 publications
(93 reference statements)
7
83
0
Order By: Relevance
“…Results of the high fire danger analysis are more pertinent for management because a small number of days characterized by extreme fire weather respond for the bulk of burned area [48]. Our results then indicate that the most dramatic variation in fire behavior between forest types (as determined by their typical surface fuel complexes) is seen under more extreme fire weather, similar to other conifer-dominated landscapes [49].…”
Section: Differences In Fire Behavior Potentialsupporting
confidence: 50%
“…Results of the high fire danger analysis are more pertinent for management because a small number of days characterized by extreme fire weather respond for the bulk of burned area [48]. Our results then indicate that the most dramatic variation in fire behavior between forest types (as determined by their typical surface fuel complexes) is seen under more extreme fire weather, similar to other conifer-dominated landscapes [49].…”
Section: Differences In Fire Behavior Potentialsupporting
confidence: 50%
“…We observed a higher reduction in burned area in years with more (and larger) fires throughout the simulation period. This is in agreement with Syphard et al (2011) and Loudermilk et al (2014) who found that fuel treatments were more effective in reducing fire severity and sequestering forest carbon under severe fire weather because of an increased number of intersections between fires and treatments.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, treatments are frequently completed on the same piece of ground over a sequence of years, highlighting the importance of modeling efforts that consider both the spatial and temporal dimensions of fuel treatment effects. A number of researchers have included temporal dynamics into simulation studies of spatiotemporal predictions of fire occurrence (Collins et al 2011, Syphard et al 2011, forest dynamics (Strom andFulé 2007, Gustafson et al 2010), and carbon sequestration (Loudermilk et al 2014). Other simulation studies tested what-if scenarios that evaluated the economic efficiency of fuel treatments (Taylor et al 2013) and anticipated the potential impacts of climate change on fire activity and forest composition (Scheller and Mladenoff 2005, Halofsky et al 2014a, Yospin et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Primarily the focus has been to use planned burning to reduce the risk from fire to human life and property situated within or adjacent to native vegetation (Fernandes and Botelho 2003;Penman et al 2011). However, additional strategies are often adopted by agencies to protect life and property such as mechanical fuel treatments (Syphard et al 2011;Syphard et al 2012;North et al 2015), community engagement (Eriksen and Prior 2013;Penman et al 2015a) and fire suppression (Calkin et al 2005;Plucinski et al 2012;Penman et al 2013b;Penman et al 2014). Several studies in Australia have found that while planned burning may reduce the extent of wildfire, the net effect is an increase in overall fire extent and frequency (Boer et al 2009;King et al 2013;Price 2015) leading to the emergence of new landscape fire regimes.…”
Section: Introductionmentioning
confidence: 99%